Measuring Individual Differences in Decision Biases: Methodological Considerations - Aczel, Balazs; Bago, Bence; Szollosi, Aba; Foldes, Andrei; Lukacs, Bence (Frontiers in Psychology, 2015)
Individual differences in people’s susceptibility to heuristics and biases (HB) are often measured by multiple-bias questionnaires consisting of one or a few items for each bias. This research approach relies on the assumptions that (1) different versions of a decision bias task measure are interchangeable as they measure the same cognitive failure; and (2) that some combination of these tasks measures the same underlying construct. Based on these assumptions, in Study 1 we developed two versions of a new decision bias survey for which we modified 13 HB tasks to increase their comparability, construct validity, and the participants’ motivation. The analysis of the responses (N = 1279) showed weak internal consistency within the surveys and a great level of discrepancy between the extracted patterns of the underlying factors. To explore these inconsistencies, in Study 2 we used three original examples of HB tasks for each of seven biases. We created three decision bias surveys by allocating one version of each HB task to each survey. The participants’ responses (N = 527) showed a similar pattern as in Study 1, questioning the assumption that the different examples of the HB tasks are interchangeable and that they measure the same underlying construct. These results emphasize the need to understand the domain-specificity of cognitive biases as well as the effect of the wording of the cover story and the response mode on bias susceptibility before employing them in multiple-bias questionnaires.